Implementasi Kebijakan Pemerintah Daerah Terhadap Penanggulangan Sampah (Studi Kasus Jln Rs Haji Percut Sei Tuan,Desa Medan Estate) - Tania Larasita Situmeang; Laurenty Simanjuntak; Rahmat Fitra Daulay; Julia Ivanna (Universitas Dehasen Bengkulu, 2023)
The Village Government plays a role in the management and implementation of government in the Village in order to realize village autonomy. The purpose of this research we are conducting is to find out how big the role of the Regional Government is in tackling waste on Jln RS Haji Medan Estate. The method in this research is descriptive research using the qualitative, where the data and information related to research issues obtained through literature studies and field visits are analyzed qualitatively, to then be interpreted according to the meaning contained in the data and information. Medan will have a bad impact on the surrounding residents. After investigating more deeply, it turns out that the village government does not care about the community, because garbage that is allowed to accumulate and scatter can be a source of disease for Medan Estate villagers. However, the material contained in the Village Head's decision letter has not been systematically which is in accordance with the standards of environmental management and protection as stipulated in Law No. 32 of 2009 concerning environmental protection and management. Therefore, we would like to review why the local government does not set special rules in the village so that it does not dispose of waste carelessly which is out of place.